Agricultural technology adoption in the Feed the Future zone in Bangladesh - Ahmed, Akhter; Hernandez, Ricardo; Naher, Firdousi (University Press Limited, 2021)
Technology is the basis for sustainable agricultural growth. Enhanced agricultural productivity and growth depend, to a large extent, upon the widespread adoption of appropriate technologies by farmers. Seed, fertilizer and irrigation technologies known as the ‘Green Revolution’ technologies have long played major roles in the growth of agriculture production in Bangladesh. The country has made commendable progress in domestic rice production through farmers’ adoption of these technologies. In the early 1970s, Bangladesh was a seriously food-deficit country with a population of about 75 million. Today, the population is more than 160 million, and Bangladesh is on the brink of self-sufficiency in rice production, which has tripled over the past three decades.